Sustaining the 'Quail Wave' in the Southern Great Plains - Dale Rollins (National Quail Symposium Proceedings, 2017)
The southern Great Plains (i.e., Texas and Oklahoma) historically affords some of the best, and currently most stable, northern bobwhite (Colinus virginianus) populations anywhere. However, bobwhite populations have declined in recent years over much of this area, especially east of the 98th meridian. Two subsets of the southern plains, the Rolling Plains (parts of northwestern Texas, western Oklahoma, and western Kansas) and the Rio Grande Plains (south Texas) offer the most expansive, contemporary northern bobwhite habitat throughout its range. Bobwhite habitat in the southern plains is affected primarily by rainfall and rangeland management for livestock. Range management practices (brush control, grazing management) can be prescribed to benefit bobwhite habitat, but a large part of potential bobwhite range in the southern plains suffers from overgrazing and excessive brush control. Farm Bill policies (e.g., Conservation Reserve Program) have had a major impact on dryland agriculture in this region, but their impacts on bobwhites have been only marginally positive (if at all) to date. Income generated from quail hunting in this region currently rivals or exceeds that generated from cattle grazing leases. Accordingly, more landowners are beginning to temper traditional land management goals, and incorporate more quail-friendly practices (i.e., ‘‘brush sculpting’’ and reducing stocking rates). Educational efforts aimed at landowners should strive to implement existing knowledge and develop informed decision-makers. The current demand for quail hunting affords an excellent opportunity to promote, and adopt, management practices that will hopefully sustain the heritage of quail hunting in this region of the bobwhite’s range for future generations.
Keywords: Callipepla squamata; Colinus virginianus; education; fragmentation; Great Plains; habitat; management; northern bobwhite; quail decline; scaled quail; Texas